Abdominal Cocoon Syndrome (Idiopathic Sclerosing Encapsulating Peritonitis): How Easy Is Its Diagnosis Preoperatively? A Case Report. (7th May 2013) - Awe, Julius A. A.
Abstract : The abdominal cocoon syndrome (or idiopathic encapsulating peritonitis) is a rare cause of intestinal obstruction. It has been reported predominantly in adolescent girls living in tropical/subtropical region in which diagnosis is only made at laparotomy in most cases. The cause and pathogenesis of the condition have not been elucidated. Prolonged administration of practalol, meconium peritonitis, and tuberculous infection of the female genital tract have been incriminated as possible causes. The author reports a case of a female patient with recurrent intestinal obstruction treated for years but failed to settle down on conservative treatment during her last hospital admission and had to undergo surgery. Preoperative diagnosis of this syndrome as the cause of her intestinal obstruction was not made until at laparotomy, when a thick fibrotic peritoneal wrapping of the bowel in a concertina-like fashion with some adhesions was found. Excision of this membrane and adhesiolysis were carried out without any need for bowel resection, and this led to relief of the obstruction and patient's complete recovery. Awareness of this benign condition in the differential diagnosis of intestinal obstruction will result in early diagnosis and correct management and prevent unnecessary bowel resections and bad outcomes.